THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN PREPARING A RESILIENT MUSLIM GENERATION IN THE ERA OF GLOBAL CHANGE - Abdi Ahadi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
The era of globalization, marked by massive social, cultural, and technological changes, demands that the younger generation—particularly Muslim youth—be well-prepared to face contemporary challenges without losing their religious identity. This article explores the role of Islamic Religious Education (IRE) in shaping a resilient, well-characterized, and adaptive Muslim generation in the face of global change. The method employed is library research by analyzing various recent and relevant scholarly journals. The findings indicate that IRE plays a strategic role in character building, strengthening moral and spiritual resilience, and enhancing the competitiveness of Muslim youth through contextual curriculum approaches, innovative teaching methods, and synergy among schools, families, and communities. This study recommends strengthening Islamic values through curriculum reform, developing teacher professionalism, and utilizing digital technology in a moderate and purposeful manner.